Selection criteria for text mining approaches. (October 2015) - Hashimi, Hussein; Hafez, Alaaeldin; Mathkour, Hassan
Highlights: Text mining include several techniques like categorization of text, clustering, etc. Text mining techniques can be used to finding useful information from documents. We propose some criteria to evaluate the effectiveness of text mining techniques. These proposed criteria can facilitate the selection of appropriate technique. Abstract: Text mining techniques include categorization of text, summarization, topic detection, concept extraction, search and retrieval, document clustering, etc. Each of these techniques can be used in finding some non-trivial information from a collection of documents. Text mining can also be employed to detect a document's main topic/theme which is useful in creating taxonomy from the document collection. Areas of applications for text mining include publishing, media, telecommunications, marketing, research, healthcare, medicine, etc. Text mining has also been applied on many applications on the World Wide Web for developing recommendation systems. We propose here a set of criteria to evaluate the effectiveness of text mining techniques in an attempt to facilitate the selection of appropriate technique.